Novel systems for position and force control of slender and compliant robots for in-situ machining - Alatorre Troncoso, David (2020)
This thesis presents a number of advances in the area of manufacturing engineering, specifically in the topic of robotics and automation, and more specifically still in the subject of feedback and control; applied to the special example of slender and compliant machining instruments for in-situ repair of gas turbines and industrial assets. A thorough literature search of in-situ repair robots, such as continuum and conventional robotic arms with material removal or non-destructive testing end effectors, is compiled and presented with particular attention to the applicability of past architectures, technologies, control methods and sensors to ``industrial minimally invasive surgery'' carried out via a borescope port. A novel robot for localised grinding of aeroengine compressor blades (boreblending) is described and analysed as a case study in-situ repair robot - an example lacking advanced position and force feedback methods and therefore limited in its capabilities and scalability. The slender probe (less than 10mm diameter and more than 100mm in length) includes a number of short continuum segments as well as rotary and prismatic stages. Following an open loop control scheme with tendon stretch compensation, the maximum position error at full deflection is 8.5% of the continuum length. Areas for improvement in position feedback, force feedback and control strategies are identified. A novel method to obtain position feedback and hence improve position accuracy, is described in the form of a shape sensor. Tubular ionic liquid stretch sensors are used as hyper-elastic strain gauges and applied as skin sensors to continuum-style robots such as those used for in-situ repair; the sensors are characterised and employed as feedback for closed-loop position control of a complex continuum arm. Closed loop trials on a complex continuum manipulator yield errors equivalent to 2.3% of continuum length, demonstrating a substantial improvement over open-loop methods. A novel method to obtain force feedback in the form of airborne sound features from a grinding end effector is then described. Calibration and signal processing of two microphone voltage lines returns a value of contact force between instrument and workpiece based on sound features such as dominant frequency and sound intensity; this force feedback is employed for closed-loop force control of a conventional robotic arm during machining. Results from the test rigs and robot arm show that such a sound-based control approach can achieve consistent cutting forces with an accuracy of 0.08N. The robot arm is shown to be capable of grinding features of consistent depth (to within 0.05mm) on beams with unknown topology. Finally, a simultaneous position-force controller is devised to make use of tubular ionic liquid stretch sensors position feedback and audible sound features force feedback to accurately machine an aeroengine compressor blade using a slender continuum arm. The parallel controller separates the task space into reactive and non-reactive directions based on the orientation of the end effector and imposes a force hierarchy and position completion threshold. The results show 80% improvement in machining time over manual methods and 33% improvement over open loop control methods.